Evaluation of WHO indicators for surveillance of acute flaccid paralysis in children: The case of Kenitra province, Morocco; from 1994 to 2018 - Jayche, Samira; Idrissi, Ahmed; Talbi, Fatima Zahra; Baghouz, Asmae; Sendaoui, Sanae; Loutfi, Amr; Dahou, Badreddine; Lahmam, Mohamed; Najy, Mohamed; Thouhami Ahami, Ahmed Omar; et al. (Bangladesh Journal of Medical Science, 2024)
Background Polio has not been detected in Morocco since 1989. The aim of this study was to examine the surveillance system for acute flaccid paralysis (AFP) in the province of Kenitra, assess its strengths and weaknesses, and suggest ways to improve it. Method & materials A qualitative and quantitative evaluation was carried out within the Kenitra Provincial Epidemiology Unit. The AFP case database was analyzed using the standards for evaluation of public health surveillance systems defined by the Centers for Disease Control and Prevention (CDC) in 2001 and WHO indicators. The surveillance system was found to be flexible and effective. Result The sensitivity of the system reached 50%, with an average notification rate of 3.04 cases. More than 40% of patients were reported within 7 days of onset of paralysis. Investigation time was approximately 70% within 48 hours of notification. 80% of stool samples were sent to the laboratory within 72 hours of collection. Conclusion: The AFP surveillance system in Kenitra is effective, adaptable and highly vigilant, allowing a rapid response. Maintaining AFP surveillance is essential until polio is eradicated worldwide. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1185-1196